Alazami syndrome in an Afghani girl: A case report and review of literature - Mazen S Alzahrani1; Lynne M Bird2 (Global Journal of Rare Diseases - Peertechz Publications, 2019)
Purpose: Alazami syndrome is a rare autosomal recessive disorder with core phenotypic manifestations of short stature, mild facial dysmorphism, and global developmental delay evolving to severe intellectual disability. Homozygous loss-of-function mutations in LARP7 gene, which encodes a chaperone protein of the noncoding RNA 7SK, have been detected in patients with Alazami syndrome. Since its fi rst description in 2012, only six families with Alazami syndrome have been reported to date. This case is reported to expand the phenotypic description to include small kidneys. Methods: The patient was referred for Clinical Genetics evaluation at Rady Children's Hospital San Diego due to intellectual disability and growth delay. Whole exome sequencing was performed (GeneDx) after informed consent.